Archaeobotanical and isotopic evidence of Early Bronze Age farming activities and diet in the mountainous environment of the South Caucasus: a pilot study of Chobareti site (Samtskhe–Javakheti region). (January 2015) - Messager, Erwan; Herrscher, Estelle; Martin, Lucie; Kvavadze, Eliso; Martkoplishvili, Inga; Delhon, Claire; Kakhiani, Kakha; Bedianashvili, Giorgi; Sagona, Antonio; Bitadze, Liana; Poulmarc'h, Modwene; Guy, André; et al.
Abstract: Recent excavation at the site of Chobareti (1615 m a.s.l., South Caucasus Mountains) reveals an important Kura-Araxes settlement and eleven burials so far, for which a first multi-proxies approach was conducted to understand both exploitation of plants and human dietary practices in this mountainous area. Thanks to the excavation of several pits, in 2011, a well-reasoned sampling for archaeobotanical analysis, including phytoliths, pollen and non-pollen palynomorphs, charcoal, seeds and other plant macroremains was undertaken. In parallel, human, animal bones and wheat seeds were recovered in order to perform stable isotope analysis (δ 13 C, δ 15 N). Results show the strong presence of cereals (especially naked wheat, as a hexaploid form, and emmer), highlighting the role played by cereal growing in the Kura-Araxes farming activities. Plant macroremains, but also phytoliths recovered in pits, reflect processing activities on the site. While animal dung seems to have been used to enhance cereal yields, different herding practices can be suggested by δ 15 N values. Whereas δ 13 C values and archaeobotanical data agree for a consumption of C3 plants, with no significant input in wheat for both animals and humans, a homogeneous mixed diet, with a great contribution of animal protein source (meat, secondary products) has been observed. Highlights: Chobareti site is an Early Bronze Age settlement (3300–2900 cal. B.C.) located at 1615 m a.s.l. in the South Caucasus. Archaeobotanical and stable isotope analysis have been performed on several pits and burials. Phytoliths, pollen and macroremains highlight the importance of cereals cultivation in these highlands. Isotope data suggest the use of manuring, differential herding practices, as well as C3 plants consumption for both animals and humans. Human dietary practices express a unique pattern with a preferential input of meat and dairy products.